Analisis Validitas Pengembangan Modul Pembelajaran Pengelasan SMAW Berbasis Proyek (Project Based Learning) - Putra, Ananda Yhuto Wibisono (LPPM Institut Pendidikan Nusantara Global, 2024)
A teaching module is a set of tools, media, methods, instructions and learning guidelines that are prepared and planned to suit the student's development phase. The following research aims to examine the feasibility of a product from developing a project-based SMAW Welding Module (PjBl) for Mechanical Engineering Vocational Education students, Faculty of Teacher Training and Education, Sultan Ageng Tirtayasa University. This research was carried out using a quantitative approach. The following research is part of research and development using the Borg and Gall method, namely Develop Preliminary Form of Product Testing using the Expert Judgment validity test. The research results were analyzed descriptively quantitatively. The research results showed that the feasibility of the module content reached 87% in the very good and very feasible category, the feasibility of the learning presentation reached 92% in the very good and very appropriate category, the appropriateness of the language reached 89% and was in the very good and very feasible category and finally based on feasibility. Graphics reached 93% so it is included in the very good and very worthy category. Overall, the conclusion is drawn that the validity of the Project-based SMAW Welding Module (PjBl) is in the very good and very feasible category and can be continued to the Preliminary Field Testing stage.